Agreement between histological subtype on punch biopsy and surgical excision in primary basal cell carcinoma. (13th June 2012) - Roozeboom, M.H.; Mosterd, K.; Winnepenninckx, V.J.L.; Nelemans, P.J.; Kelleners‐Smeets, N.W.J.
Abstract Background Diagnosis of clinically suspected basal cell carcinoma (BCC) by histological confirmation with punch biopsy has been recommended before treatment. Even shave biopsy has been proposed as useful to predict the correct subtype in primary BCC in 76–81%, whereas the agreement between histological BCC subtype on punch biopsy and subsequent excision specimens in recurrent BCC is 67.1%. However, no large studies on the agreement between histological BCC subtype seen on punch biopsy and the following surgical excision are performed in primary BCC. Objective The aims of this study were (i) to establish the agreement between histological BCC subtype on punch biopsy and the subsequent surgical excision of primary BCC and; (ii) to investigate the proportion of primary BCCs in which punch biopsy enables identification of the most aggressive growth pattern. Methods Retrospective analyses of 243 primary BCCs with both punch biopsy and subsequent surgical excision. Analyses were based on the most aggressive histological subtype of the tumour. Results The agreement between BCC subtype on punch biopsy and the subsequent surgical excision of primary BCCs was 60.9%. A punch biopsy can predict the most aggressive growth pattern of primary BCCs in 84.4%. Seventy‐four percentage of all primary BCCs consisted of more than one histological subtype. Conclusion Dermatologists and other physicians have to be aware of the limited diagnostic value of a punch biopsy to determine the histological BCC subtype of the whole lesion. Misdiagnosis of the subtype will lead to undertreatment in one of six primary BCCs.